Formación en competencias investigativas como estrategia pedagógica de la educación comprometida con el bienestar social: Training in Research Competences as a Pedagogical Strategy for Education Committed to Social Welfare - Infante Rivera, Lipselotte de Jesús (Universidad del Zulia, 2021)
The following research analyzes the importance of properly training students in research skills, in order to improve the living conditions shared by society. Training in these skills is characterized as having an irreducible education that serves individual and social training and liberation projects. In this sense, so that learning in capacities are strengthened over time, its inclusion as cross-curricular knowledge is requested; contributing and determining school success. We validate inquiry, cooperation, the study of bibliographic material, the ability to design and carry out essays; as preferred cognitive skills that favor investigations. This is a bibliographic research from the rationalist-deductive approach.